1998
DOI: 10.1016/s0006-3207(97)00094-3
|View full text |Cite
|
Sign up to set email alerts
|

Extensive predator persecution caused by population crash in a game species: The case of red kites and rabbits in Spain

Abstract: The European rabbit Oryctolagus cuniculus, an important game species in Spain, has declined sharply since the arrival of haemorrhagic disease in 1988. As a consequence of this decline, it appears that illegal and extensive persecution of predators has increased. We have assessed the impact of this persecution on red kites Milvus milvus.Around 90% of the populations studied have declined during the last 3-10 years, and the species' range has been reduced since 1980, particularly in high rabbit density areas (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
149
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(158 citation statements)
references
References 18 publications
5
149
0
4
Order By: Relevance
“…The control of nongame predator species and the use of other methods (e.g., poisoning) are strictly prohibited according to the legislation (although sometimes there are exceptional permits to control other species, such as some rodents). However, illegal predator killing by hunters has been frequently documented in central-southern Spain (Villafuerte et al 1998, Márquez et al 2012, and indeed it is considered among the main causes explaining the decline of some endangered predators. For example, the analysis of 267 records of nonnatural mortality of the Spanish imperial eagle over a 16-yr period (1989-2004) showed that near 40% of the deaths were caused by predator control, and almost all of them occurred in central-southern Spain (González et al 2007).…”
Section: Context and Study Areamentioning
confidence: 99%
“…The control of nongame predator species and the use of other methods (e.g., poisoning) are strictly prohibited according to the legislation (although sometimes there are exceptional permits to control other species, such as some rodents). However, illegal predator killing by hunters has been frequently documented in central-southern Spain (Villafuerte et al 1998, Márquez et al 2012, and indeed it is considered among the main causes explaining the decline of some endangered predators. For example, the analysis of 267 records of nonnatural mortality of the Spanish imperial eagle over a 16-yr period (1989-2004) showed that near 40% of the deaths were caused by predator control, and almost all of them occurred in central-southern Spain (González et al 2007).…”
Section: Context and Study Areamentioning
confidence: 99%
“…Nevertheless, the illegal removal of some predators of conservation concern, including raptors and carnivores, has frequently been reported (e.g. Villafuerte et al 1998, Márquez et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…During the last century, bird populations have been affected by different kinds of disturbances and impacts due to man-made structures such as highways (Fajardo et al 1998), power lines (Ferrer et al 1991;Janss and Ferrer 1998;Penteriani 1998), radio / television towers (Stahlecker 1979;Smith 1985;Nelson and Curry 1995), wind farms (Orloff and Flannery 1992), glass windows (Klem 1990a(Klem , 1990b, and due to human activities such as poisoning (Harmata et al 1999) and illegal shooting (Villafuerte et al 1998). The increasing mortality of birds by human structures has generated an important literature evaluating the impact of these elements on bird populations and developing the application of protective measures (Klem 1990b;Fajardo et al 1998;Alonso and Alonso 1999).…”
Section: Introductionmentioning
confidence: 99%